Experiments on the introduction of a rare, endangered, narrow-endemic plant Rosa iliensis chrshan. in the conditions of the steppe zone of Zailiysky Alatau (Experimental biology, 2020)
The article deals with the introduction of a rare, endangered, narrow-endemic plant Rosa iliensis Chrshan. by seed in the conditions of the steppe zone of the ZailiyskyAlatau. It is noted that the results of the study were positive. Although only 10 to 20% of the 100 seeds sown were sprouted, but 90 to 99% of the sprouts that appeared successfully took root. This makes it possible to consider the introduction of Rosa iliensis Chrshan. in the future seminal way of great optimism. Moreover, by entering Rosa iliensis Chrshan. during the introduction, we can simultaneously solve several important issues.The main ones, save Rosa iliensis Chrshan. from extinction; creating an artificial Rosa iliensis Chrshan plantation. we will provide the vitamin industry and pharmaceutical industry of the Republic of Kazakhstan with natural and cheap raw materials; Rosa iliensis Chrshan. we can recommend landscaping of parks, squares, alleys of cities, district centers and remote localities; introducing Rosa iliensis Chrshan. into the introduction in the Botanical gardens of the Republic of Kazakhstan, it can be used as a Queen for crossing with cultural varieties in order to breed new varieties of Kazakhstan garden roses.Keywords: introduction, population, endemic plants, stratification, cuttings